Everolimus with early withdrawal or reduced‐dose calcineurin inhibitors improves renal function in liver transplant recipients: A systematic review and meta‐analysis. Issue 2 (18th January 2017) - Lin, Michael; Mittal, Sahil; Sahebjam, Farhad; Rana, Abbas; Sood, Gagan K.
Abstract: Calcineurin inhibitors (CNI) are the mainstay of immunosuppression after liver transplantation (LT), but CNIs are associated with significant nephrotoxicity. Recently, mTOR inhibitors such as sirolimus and everolimus (EVR) have been used with or without CNIs in LT recipients for their renal‐sparing effect. We conducted a systematic review and meta‐analysis of randomized controlled trials (RCT) that examined the effect of EVR with CNI minimization or withdrawal on renal function in LT recipients. RCT of primary adult LT recipients with baseline GFR >30 mL/min who received EVR with CNI minimization or withdrawal were included. Four RCTs (EVR n=465, control n=428) were included. In three RCTs, EVR was initiated 4 weeks following LT; these studies were used to assess the primary outcome. All four studies were used to assess the secondary outcomes. Based on this study, EVR use with CNI minimization in LT recipients is associated with improved renal function at 12 months by GFR of 10.2 mL/min (95% CI: 2.75‐17.8). EVR use was not associated with an increased risk of biopsy‐proven acute rejection (RR 0.68, 95% CI: 0.31‐1.46), graft loss (RR 1.60, 95% CI: 0.51‐5.00), or mortality (RR 1.34, 95% CI 0.62‐2.90). However, it was associated with an increased risk of overall infections (RR 1.45, 95% CI: 1.10‐1.91).